Characterization of odorants in human urine using a combined chemo-analytical and human-sensory approach: a potential diagnostic strategy. - Wagenstaller, Maria; Büttner, Andrea (Metabolomics, 2013)
The volatile and odorous profile of human urine may be a rich source for physiological information and could increase our understanding of metabolization and excretion processes of low-molecular weight compounds originating from, for example, dietary or endogenous sources. However, the diagnostic potential of the urinary volatile fraction is not yet fully understood, probably due to the limited application of modern analytical tools in urine volatile analysis. Accordingly, the aim of this study was to evaluate a combined chemo-analytical and human-sensory approach for characterization of the human urine odorant composition. We used one- and two-dimensional high resolution gas chromatography–olfactometry/mass spectrometry to identify commonly occurring and potent odorants in human urine. The studies were carried out on both native urine and on urine that had been treated by glucuronidase assays, with analysis of the liberated odor-active compounds using the same techniques. Based on retention indices, odor qualities and intensities, and mass spectra compared to references, a total of 14 odorants were detected in the majority of the untreated urine samples, and 24 odorants in the glucuronidase-treated samples. A major part of the identified substances are reported here for the first time. Our results show that chemosensory approaches are a useful strategy for the characterization of the odorant profile of human urine.<br